2019
DOI: 10.1071/sr19002
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen fertilisation improves the grain production efficiency and sustainability of out-of-season corn and Congo grass intercropping

Abstract: Intercropping is a method for straw production and maintenance during the dry season in no-tillage systems. Among the crops used for intercropping are corn and grasses. However, nitrogen can interfere with the production capacity of these plants. The objective of this study was to evaluate the macronutrient accumulations and efficiency values of out-of-season corn and Congo grass intercropped under a no-tillage system as a function of the nitrogen fertilisation applied by side dressing. The experimental design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…This result shows the need of N fertilization in the secondcrop corn intercropped with ruzigrass. Batista et al (2019b) found that second-crop corn intercropped with ruzigrass requires N fertilization management to complement the amount of N provided by the soil, to minimize the competition for this nutrient. Nitrogen rates on the agronomic performance of second-crop corn single and intercropped with ruzigrass or showy rattlebox…”
Section: Resultsmentioning
confidence: 99%
“…This result shows the need of N fertilization in the secondcrop corn intercropped with ruzigrass. Batista et al (2019b) found that second-crop corn intercropped with ruzigrass requires N fertilization management to complement the amount of N provided by the soil, to minimize the competition for this nutrient. Nitrogen rates on the agronomic performance of second-crop corn single and intercropped with ruzigrass or showy rattlebox…”
Section: Resultsmentioning
confidence: 99%
“…In the face of the reality of the low level of agricultural scale operation [1], high cost of grain production [2,3], and lack of a young and middle-aged labor force in rural areas [4][5][6], how to realize the transformation of agricultural operation modes and the improvement of grain production efficiency has become an important problem to be solved urgently [7][8][9]. The development of APTS and the promotion of service scale operation are the keys to answering this question [10].…”
Section: Introductionmentioning
confidence: 99%
“…Choosing a suitable intercropping system for each case is quite complex, as its success depends on interactions between the species used, management practices adopted, and environmental conditions (Iqbal et al, 2019). Intercropping of maize (Zea mays) with grasses in a pasture renovation and straw production for a no-tillage system is a recent practice, which has been widely studied in Brazil (Pereira et al, 2016;Batista, Giacomini, Gerdes, Mattos, & Otsuk, 2019;Rocha et al, 2020;Sapucay et al, 2020). However, intercropping grasses with soybeans is still a challenge due to the small size of soybean plants and low competition capacity (Machado, Cecato, Comunello, Concenço, & Ceccon, 2017).…”
Section: Introductionmentioning
confidence: 99%